Estimated energy balance of international female rugby sevens players in training and competition scenarios - Curtis, C.; Arjomandkhah, N.; Cooke, C.; Russell, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Rugby sevens is a contact sport comprising of two teams of seven players who compete over two 7-min halves. Rugby sevens players experience accentuated loads during match-play, with mean total distances of appr.113-120 m x min-1 covered. Likewise, appr. 30% of total match distances are covered at speeds >/=5 m s-1, while 39% more high velocity (>/=4 m s-2) accelerations are performed when players compete in international tournaments. Accordingly, to facilitate optimised performance during match-play and realisation of training-induced adaptations, the energy balance of rugby sevens players needs consideration. However, limited data currently exists regarding the energy intake (EI) and expenditure (EE) of rugby sevens players in both training and competitive scenarios, especially in the case of female players. Therefore, this two-part study aimed to estimate EI and EE in international female rugby sevens players during a) a training camp (n = 11), and b) an international competition (n = 8) held within 14 days of each other.